Implementation of Public Private Partnership in The Management Market RAU (Rau Trade Center) In Serang City - . Rahmawati (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
According to the approach of New Public Service, the government's main focus is public service. As an institution in charge of providing services to the public, the government certainly can not do it all by itself or single fighter. This is because many types of services that must be provided to the public. Therefore do a cooperation contract between the government and the private sector (KSP) in supplying and servicing the public. Memorandum of understanding contract between the government and private or Public Private Partnership (PPPs) considered very necessary to organize public services, as well as the procurement and management of Rau Market (Rau Trade Center). Besides as icons Kota Serang, Rau Trade Center also serves as a tool in the development of the local economy. This study uses the theory of policy implementation according to Charles O. Jones, namely the organization, interpretation and application. The method used is qualitative case study approach. The results showed that the form of cooperation between the government of Kota Serang with PT. Pesona Banten Persada in the management of rau market is Build Operate Transfers with a concession period of 20 years since 2002. The cooperation is carried out to increase the economic activity of society to accommodate many traders. Rau market management differentiated by region in the building is the responsibility of the private sector and the authorities covering the costs of lease / sale price rental kiosks and stalls, hygiene management of garbage and cleanliness and parking levy withdrawal. Outside the building into the management of local authorities in terms of cleanliness and parking levies, while for rental kiosk / los beyond the authority of the local government because it is owned by an individual. Contributions partnership on revenue of Serang not optimal, amounting to 300 million per month from the levy cleanliness and parking. There has been no further decisions regarding the management of rau by the private market will continue or will be submitted to the local government after the concession period ends.